Answer:
320
Step-by-step explanation:
320 words per minute 40x8=320
Answer:
a. (3,11) (4,15) (5,19) (6,23)
b. it's not proportional because b (from y=mx+b) is not 0
c. the equation is y = 4x - 1
d. graph the y-int (-1) on the y-intercept and then connect the points in a.
Step-by-step explanation:
The Pythagorean theorem is the idea that the sum of the two legs which are both squared is equal to the hypotenuse's length squared.
*<em>look at the image I attached for a better explanation</em>
By looking at the picture, we are missing the leg's length, and by using the Pythagorean theorem, we get the equation
Thus the <u>missing side length is 12 cm</u>
Hope that helps!
The solution is the point of intersection between the two equations.
Assuming you have a graphing calculator or a program to lets you graph equations (I use desmos) you simply put in the equetions and note down the coordinates of the point of intersection.
In the graph the first equation is in blue and the second in red.
The point of intersection = the solution = (-6 , -1)
If you dont have access to a graphing calculator you could draw the graphs by hand;
1) Draw a table of values for each equation; you do this by setting three or four values for x and calculating its image in y (you can use any values of x)
y = 0.5 x + 2 (Im writing 0.5 instead of 1/2 because I find its easier in this format)
x | y
-1 | 1.5 * y = 0.5 (-1) + 2 = 1.5
0 | 2 * y = 0.5 (0) + 2 = 2
1 | 2.5 * y = 0.5 (1) + 2 = 2.5
2 | 3 * y = 0.5 (2) + 2 = 3
y = x + 5
x | y
-1 | 4 * y = (-1) + 5 = 4
0 | 5 * y = (0) + 5 = 5
1 | 6 * y = (1) + 5 = 6
2 | 7 * y = (2) + 5 = 7
2) Plot these point on the graph
I suggest to use diffrent colored points or diffrent kinds of point markers (an x or a dot) to avoid confusion about which point belongs to which graph
3) Using a ruler draw a line connection all the dots of one graph and do the same for the other
4) The point of intersection is the solution
Answer:
Step-by-step explanation:
common difference d=3-1=2
first term a=1
an=a+(n-1)d
2n-1=1+(l-1)2
2n-1=1+2l-2
2n-1=2l-1
l=n
(i used l for number of terms)
number of terms=n